Cutaneous protothecosis in a patient with previously undiagnosed HIV infection. (4th March 2014) - Fong, Kenneth; Tee, Shang‐Ian; Ho, Madeline S L; Pan, Jiun Yit
Abstract Protothecosis is an uncommon condition resulting from infection by achlorophyllous algae of the Prototheca species. Immunocompromised individuals are generally most susceptible to protothecal infection and tend to develop severe and disseminated disease. However, the association between protothecosis and HIV‐induced immunosuppression is not clear, with only a handful of cases having been described to date. Here we report a case of cutaneous protothecosis in a Chinese man with previously undiagnosed HIV infection that responded well to oral itraconazole.